PeV neutrinos from the propagation of ultra-high energy cosmic rays - Roulet, Esteban (2013)
We discuss the possibility that the PeV neutrinos recently observed by IceCube are produced by the interactions of extragalactic cosmic rays during their propagation through the radiation backgrounds. We show that the fluxes resulting from the decays of neutrons produced in the interactions of cosmic ray protons with the CMB background are suppressed (Eν2dΦν/dE < 10−10 GeV/cm2 s sr), with those resulting from the decays of pions produced in the interactions with the UV/optical/IR backgrounds being the dominant ones at PeV energies. The anti-neutrino fluxes produced by the decay of neutrons resulting from the photodisintegration of heavy nuclei with CMB photons are also shown to be quite suppressed (Eν2dΦν/dE < 10−11 GeV/cm2 s sr), while those produced by photo-pion processes with UV/optical/IR backgrounds may be larger, although they are not expected to be above those achievable in the pure proton case. Scenarios with mixed composition and low cutoff rigidities can lead to PeV neutrino fluxes enhanced with respect to those in the pure Fe scenarios. We also discuss the possible impact of the Glashow resonance for the detection of these scenarios, showing that it plays a moderate role.